Convergent evolution and horizontal gene transfer in Arctic Ocean microalgae - Dorrell, Richard G; Kuo, Alan; Füssy, Zoltan; Richardson, Elisabeth H; Salamov, Asaf; Zarevski, Nikola; Freyria, Nastasia J; Ibarbalz, Federico M; Jenkins, Jerry; Pierella Karlusich, Juan Jose; Stecca Steindorff, Andrei; Edgar, Robyn E; et al. (Life science alliance, 2023)
Microbial communities in the world ocean are affected strongly by oceanic circulation, creating characteristic marine biomes. The high connectivity of most of the ocean makes it difficult to disentangle selective retention of colonizing genotypes (with traits suited to biome specific conditions) from evolutionary selection, which would act on founder genotypes over time. The Arctic Ocean is exceptional with limited exchange with other oceans and ice covered since the last ice age. To test whether Arctic microalgal lineages evolved apart from algae in the global ocean, we sequenced four lineages of microalgae isolated from Arctic waters and sea ice. Here we show convergent evolution and highlight geographically limited HGT as an ecological adaptive force in the form of PFAM complements and horizontal acquisition of key adaptive genes. Notably, ice-binding proteins were acquired and horizontally transferred among Arctic strains. A comparison with Tara Oceans metagenomes and metatranscriptomes confirmed mostly Arctic distributions of these IBPs. The phylogeny of Arctic-specific genes indicated that these events were independent of bacterial-sourced HGTs in Antarctic Southern Ocean microalgae.
Keywords: Microalgae; Gene Transfer, Horizontal; ledový příkrov; Arctic Regions; Bacteria; Ice Cover; mikrořasy; oceány a moře; Oceans and Seas; přenos genů horizontální; Arktida